Audit of the outcome of peptic ulcer disease diagnosed 10 to 20 years previously. Issue 6 (June 1996) - Malliwah, J A; Tabaqchali, M; Watson, J; Venables, C W
Abstract : METHODS/AIMS: During 1993-1994 an audit of the outcomes of a consecutive series of peptic ulcer patients, first diagnosed endoscopically between 1972-1983, was carried out. Three hundred and thirty six patients fitting the entry criteria were identified, 46 had died in the interval, and 44 were lost to follow up, leaving 246 available for evaluation. All patients completed questionnaires on their current symptomatic state, drug treatment, and details of any operations they had undergone since their original diagnosis. In addition they were asked to indicate, on an analogue scale, their overall assessment of how their ulcer problem was affecting them at the time of the review. Where available hospital records were obtained and analysed for any further admissions and the results of any further endoscopies. RESULTS: Of the 246 patients, 158 were men and 88 female. Duodenal ulcers (DU) were present in 204 and gastric ulcers (GU) in 51 (nine had both a DU and GU). Since the diagnosis 65 patients had undergone surgical treatment: 44 for poor ulcer control, nine for pyloric stenosis, nine for a perforation, one for a major gastrointestinal bleed, and two for a gastric carcinoma developing within two years of the diagnosis of a GU. The overall incidence of ulcer complications during this follow up period (excluding the carcinomas) was 7.7%. Initial medical treatment was with histamine H2 blockade in 234 patients–87.4% cimetidine (C) and 11% ranitidine (R)–with other agents in the remainder. At follow up 176 patients were still receiving medical treatment (C, 71%: R, 22%, other, 7%) including 30 who had previously undergone a definitive surgical procedure. Dyspeptic symptoms were recorded in 50.4% of the patients, abdominal pain being the commonest complaint. There was a significant relation between abdominal pain and the analogue scores provided by the patients with significantly more (p = 0.02) of those who had undergone surgical treatment recording this as a continuing problem (44.6% v 36%). CONCLUSION: There is no evidence provided by this study that, in these patients, their ulcer disease is undergoing spontaneous remission with time.